Edutour in Kauman Village: Transforming Tradition and Education into Friendly Tourism in Kudus City - Eriyani; Lola Kurnia Pitaloka; Kardoyo (Indonesian Journal of Devotion and Empowerment, 2025)
This community engagement program aims to develop Kauman Village in Kudus City as an educational tourism village based on historical heritage and traditional arts through a participatory training approach. The program was implemented in three stages: preparation, implementation, and evaluation. The preparation stage involved coordination and Focus Group Discussions (FGDs) with the Kudus Regency Department of Culture and Tourism, village authorities, and the youth organization (Karang Taruna). The implementation stage focused on historical storytelling training, digital media literacy enhancement, and the production of tourism promotional content grounded in local narratives. Evaluation was conducted through observation, interviews, and joint reflection with community partners. The FGD results emphasized the importance of mapping supporting villages within the Menara Kudus heritage area to avoid overlapping tourism routes. Based on this mapping, Kauman Village was designated as a historical tourism zone, highlighting narratives of Islamic dissemination and Hindu–Islamic cultural acculturation. The training activities improved participants’ understanding of local history, communication skills, and digital literacy. Program outputs included a historical narrative module and storytelling videos used for educational and digital promotional purposes. Overall, the program demonstrates that community-based training supported by local narratives and digital technology effectively promotes sustainable historical tourism village development.